2013
DOI: 10.1097/qad.0b013e32835bc535
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a fourth-generation HIV screening assay and an alternative HIV diagnostic testing algorithm

Abstract: The alternative testing algorithm improved early infection sensitivity and identified HIV-2 infections. Two potential false-positive algorithm results occurred with western blot-indeterminate specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…This study demonstrated that the proposed laboratory-based algorithm performs well in high-risk populations and the incorporation of NAAT improved the detection of acute infections. These data add to several previous studies [6,[20][21][22] to further support the use of the CDC proposed algorithm. The results also substantiate previous findings regarding reduced sensitivity of OF testing during acute infection and in the presence ARVs [28][29][30][31][32][33] and highlight the importance of selecting the right sample type and diagnostic tests when choosing testing strategies in populations with high rates of acute infection and potential confounding effects of ARVs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study demonstrated that the proposed laboratory-based algorithm performs well in high-risk populations and the incorporation of NAAT improved the detection of acute infections. These data add to several previous studies [6,[20][21][22] to further support the use of the CDC proposed algorithm. The results also substantiate previous findings regarding reduced sensitivity of OF testing during acute infection and in the presence ARVs [28][29][30][31][32][33] and highlight the importance of selecting the right sample type and diagnostic tests when choosing testing strategies in populations with high rates of acute infection and potential confounding effects of ARVs.…”
Section: Discussionsupporting
confidence: 79%
“…The proposed algorithm has detected more HIV-1 infections in different populations [6,20]. In addition, the sensitivity and specificity of the algorithm in established infections has been shown to be higher than 99% [6].…”
Section: Introductionmentioning
confidence: 89%
“…In addition, to assess performance for detecting early infection, well-characterized HIV-1 seroconversion panels from the US (presumably subtype B) were obtained from Zeptometrix, Inc. (Buffalo, NY) and BBI-SeraCare Diagnostics [12][13][14]. As previously reported, each panel had at least one specimen that was WB indeterminate (9 seroconverters with 64 total specimens) or WB positive (17 seroconverters with 166 total specimens) and all panels had at least one specimen that was HIV-1 NAT-only positive.…”
Section: Sample Setsmentioning
confidence: 99%
“…For routine HIV testing, a laboratory-based fourth generation (antigen/antibody combination) assay that detects HIV p24 antigen and HIV antibodies should be used and if reactive, should be followed by a confirmatory HIV-1/HIV-2 antibody differentiation immunoassay in the first step (Figure 2) [27,30,31].…”
Section: Hiv Nucleic Acid Testsmentioning
confidence: 99%